Pembinaan Kreatif Promosi Dengan Digital Copywriting Di Panti Asuhan Islam Media Kasih, Tangerang - Radita Gora; Muhammad Abdurrohim; Oni Tarsani; Sri Desti Purwatiningsih (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The existence of orphanage youth is often considered as children who are full of compassion and are considered as backward in terms of obtaining education and technological progress. So that teenagers who become students assisted by orphanages need to get learning and coaching competence in expertise, especially in terms of building digital talent and following current digital technology developments. Efforts to build coaching for students assisted by this orphanage as well as a briefing in the world of work, so students are assisted through digital copywriting training in creating digital talent for teenagers who live in orphanages. This training is in the form of creative writing training on advertisements and making ad captions to persuade the audience. Based on the results of the training, it shows that the students assisted by the Media Kasih Islamic Orphanage have high enthusiasm in learning and also practice making digital copywriting for posts on social media that are introduced from creative thinking, looking for inspiration for words, introduction to digital marketing to create text for ads such as making taglines and short sentences.